Web-Based Student Internship Monitoring Information System (Case Study: SMK Ma'arif NU 2 Boyolali) - Dewi, Fany Kusuma; Hanifah, Rahma Nurhuda (LPPM STIKI Malang, 2024)
Internships are an essential component of vocational school programs, including at SMK Ma'arif NU 2 Boyolali, where students engage in six-month fieldwork during the 12th grade. The current monitoring process relies on WhatsApp and manual documentation, including paper-based journals for attendance, daily activity logs, and final report submissions. This manual approach is inefficient and complicates data management for supervisors. This research aims to develop a web-based information system to streamline the monitoring and management of student internships. The study employs observation, interviews, and literature review for data collection, alongside the SDLC method for system development through planning, analysis, design, implementation, and maintenance. The system provides three user roles: admins manage data and reports; students log attendance, activities, and submit reports; and supervisors verify submissions. Black box testing confirmed functional success, while user testing yielded an average satisfaction score of 87.53%, demonstrating the system's effectiveness and usability.